Case Report: De Clerambault's Syndrome in Dementia With Lewy Bodies - Suehiro, Takashi; Satake, Yuto; Hashimoto, Mamoru; Ikeda, Manabu (Frontiers in Psychiatry, 2021)
Background: Erotomania, also known as de Clerambault's syndrome, is characterized by the delusion that a person has fallen in love with the patient. It occasionally appears secondary to psychiatric disorders and organic brain diseases. However, there have been no reports on cases secondary to dementia with Lewy bodies (DLB). Case Presentation: The patient was an 83-year-old woman who lived alone. Mild cognitive impairment appeared at the age of 82 years. Soon after, she had the delusional conviction that her family doctor was in love with her. Her symptoms, such as gradually progressive cognitive impairment, cognitive fluctuations, and parkinsonism, indicated DLB. She was treated with a small dose of antipsychotic agents. Conclusions: This case report suggests the possibility of de Clerambault's syndrome during the early stages of DLB. Further investigations are required to clarify the mechanism and treatment of de Clerambault's syndrome in patients with DLB.